As políticas brasileiras sobre drogas e sua dimensão assistencial sob um olhar crítico dialético: da República Velha à reforma psiquiátrica (1889-2001) - Aleixo, Aleff Silva (2021)
Since 2013, Brazilian drug policies passed through deep changes that can be condensed to the subsumption of their dimension of care to assistance regimes based on abstinence, prohibition and asylum, which goes against the principles contained in the Unified Health System (SUS), the Brazilian Psychiatric Reform (RPb) and the Universal Declaration of Human Rights. These changes come in the wake of a neoliberal counter-reformist restructuring of the entire Brazilian state, as well as its economic base. Thus, the present research had as main objective understand how a paradigm of assistance to people with problems resulting from the use of drugs worldwide recognized and supported could be replaced by a dated, proven harmful and ineffective assistance regime that very much resembles the past of our country. For that, we made use of a historical examination, in the light of the historical-dialectical materialism, of the Brazilian laws on drugs from the proclamation of the republic until the year 2001 (the "before" of what we lived before), paying attention to the form how the assistance dimension appears in these devices. Thus, associating such policies with the structural movements of the Brazilian social formation, which is colonial/dependent, and with capitalism as a social totality, we were able to point out that the repression of people who habitually use drugs, especially their poor and black fractions, fulfills a central role to the maintenance of the Brazilian class structure since its dawn, configuring itself, therefore, as an opportune resource for the updating and widening of the social abyss that marks our sociability. With regard to drug policies, especially in their assistance, the relative progress experienced between 2001 and 2016, when put into perspective, is, in fact, an exception that, up to the present moment, confirms the Brazilian rule.